Analisis Pola Kinerja Anak dalam Tes Membaca untuk Mengidentifikasi Anak yang Membutuhkan Pendampingan Dini Menggunakan Algoritma K-Means Clustering di PAUD Seroja - Sarimole, Frencis Matheos; Septiansyah, Muhamad Aqil (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to analyze children's performance patterns in reading tests in order to identify children who need early assistance at PAUD (Early Childhood Education) Seroja. Early identification is very important to provide timely assistance to children who have reading difficulties, so as to improve their reading abilities from an early age. In this research, the K-Means Clustering algorithm was used to group children based on their reading test results. The data used in this research consisted of reading test results taken from a number of children at PAUD Seroja. K-Means Clustering algorithm is applied to Cluster children into groups based on their performance. The results of this grouping are then analyzed to identify significant performance patterns and to identify children who need early assistance.